2006
DOI: 10.1029/2005tc001927
|View full text |Cite
|
Sign up to set email alerts
|

Precollisional, multistage exhumation of subducted continental crust: The Sesia Zone, western Alps

Abstract: The Sesia Zone within the Tertiary arc of the western Alps is a relic of the subducted part of the Adriatic continental margin along the SE border of the Tethyan ocean. The Sesia Zone comprises three basement nappes which individuated during Late Cretaceous (65–80 Ma) subduction to different depths at high‐pressure (HP, blueschist, eclogite facies) conditions (peak pressures of 1.0–1.2, 1.0–1.5, and 1.5–2.0 GPa). The thrusts bounding these nappes developed where the crust was previously thinned during Jurassic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
139
1
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(147 citation statements)
references
References 68 publications
6
139
1
1
Order By: Relevance
“…Except for Rim1 in FG1249, all of the garnet rims modelled are found to be stable at eclogite facies conditions that are similar to those recently determined for the central Sesia Zone (e.g. KonradSchmolke et al, 2006;Konrad-Schmolke and Halama, 2014;Regis et al, 2014;Rubatto et al, 2011;. In the following, the main textures recognized in garnet are discussed and related to specific processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Except for Rim1 in FG1249, all of the garnet rims modelled are found to be stable at eclogite facies conditions that are similar to those recently determined for the central Sesia Zone (e.g. KonradSchmolke et al, 2006;Konrad-Schmolke and Halama, 2014;Regis et al, 2014;Rubatto et al, 2011;. In the following, the main textures recognized in garnet are discussed and related to specific processes.…”
Section: Discussionmentioning
confidence: 99%
“…The fourth zone was modelled as stable at 550 • C and 1.7-2.2 GPa; hence it is certainly Alpine in age, as pre-Alpine metamorphism had not reached eclogite facies conditions. Similar garnet zoning was interpreted differently by KonradSchmolke et al (2006), who concluded that the zones do not reflect two orogenic cycles but are related to different water contents of the protoliths during Alpine HP subduction. In water-saturated rocks garnet would then display typical prograde zoning, whereas in water-undersaturated rocks garnet would produce more complex zoning, including abrupt compositional changes from core to rim.…”
Section: Geological Setting and Previous Work On Garnetmentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, another tectonic unit has been identified in the southern SLZ: the Rocca Canavese Thrust Sheet (RC of Pognante 1989a, 1989b. A redefinition of these metamorphic complexes has been proposed by Babist, Handy, Konrad-Schmolke, and Hammerschmidt 2006.…”
Section: Geologic Outlinementioning
confidence: 99%
“…The effects of slab failure are important, diverse, and may be responsible for features such as rapid uplift (Chatelain et al 1992), syncollisional magmatism (Davies and von Blanckenburg 1995;Keskin 2003;Macera et al 2008), tomographic gaps in the descending slab (Wortel and Spakman 1992), thick-skinned foreland deformation (Cloos et al 2005), seismic discontinuities (Wortel and Spakman 1992), crustal recycling (Hildebrand and Bowring 1999), transitory pulses of mafic magmatism (Ferrari 2004) doubly vergent orogens (Regard et al 2008), plateau uplift (Rodgers et al 2002), ultra-high pressure exhumation Babist et al 2006;Xu et al 2010), changes in plate motion (Austerman et al 2011); subhorizontal swarms of deep earthquakes (Chen and Brudzinski 2011), lateral shifts in foredeep sedimentation (van der Meulen et al 1998), opening of small ocean basins (Carminati et al 1998), switchover from foredeep flysch to orogenic molasse (Sinclair 1997;Wilmsen et al 2009), and porphyry copper and other mineralization (Solomon 1990;de Boorder et al 1998;Cloos et al 2005;Hildebrand 2009). …”
Section: Slab Failurementioning
confidence: 99%